Impact of Fractional Flow Reserve Derived From Coronary Computed Tomography Angiography on Heart Team Treatment Decision-Making in Patients With Multivessel Coronary Artery Disease: Insights From the SYNTAX III REVOLUTION Trial. (December 2019) - Andreini, Daniele; Modolo, Rodrigo; Katagiri, Yuki; Mushtaq, Saima; Sonck, Jeroen; Collet, Carlos; De Martini, Stefano; Roberto, Maurizio; Tanaka, Kaoru; Miyazaki, Yosuke; Czapla, Jens; Schoors, Danny; et al.
Abstract : Background: Fractional flow reserve (FFR) is a reliable tool for the functional assessment of coronary stenoses. FFR computed tomography (CT) derived (FFRCT ) has shown to be accurate, but its clinical usefulness in patients with complex coronary artery disease remains to be investigated. The present study sought to determine the impact of FFRCT on heart team's treatment decision-making and selection of vessels for revascularization in patients with 3-vessel coronary artery disease. Methods: The trial was an international, multicenter study randomizing 2 heart teams to make a treatment decision between percutaneous coronary interventions and coronary artery bypass grafting using either coronary computed tomography angiography or conventional angiography. The heart teams received the FFRCT and had to make a treatment decision and planning integrating the functional component of the stenoses. Each heart team calculated the anatomic SYNTAX score, the noninvasive functional SYNTAX score and subsequently integrated the clinical information to compute the SYNTAX score III providing a treatment recommendation, that is, coronary artery bypass grafting, percutaneous coronary intervention, or equipoise coronary artery bypass grafting-percutaneous coronary intervention. The primary objective was to determine the proportion of patients in whom FFRCT changed the treatment decision and planning. Results: Overall, 223 patients were included. Coronary computed tomography angiography assessment was feasible in 99% of the patients and FFRCT analysis in 88%. FFRCT was available for 1030 lesions (mean FFRCT value 0.64±13). A treatment recommendation of coronary artery bypass grafting was made in 24% of the patients with coronary computed tomography angiography with FFRCT . The addition of FFRCT changed the treatment decision in 7% of the patients and modified selection of vessels for revascularization in 12%. With conventional angiography as reference, FFRCT assessment resulted in reclassification of 14% of patients from intermediate and high to low SYNTAX score tertile. Conclusions: In patients with 3-vessel coronary artery disease, a noninvasive physiology assessment using FFRCT changed heart team's treatment decision-making and procedural planning in one-fifth of the patients. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02813473. Abstract : Supplemental Digital Content is available in the text.